Manajemen Media Pembelajaran Digital dalam Mewujudkan Efektivitas dan Semangat Belajar pada Masa Pandemi di Raudthatul Athfal Kecamatan Kalipucang Pangandaran - Lilis Gunawati (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
This study aims to determine the planning of digital learning media, implementation of digital learning media, and evaluation of digital learning media in relation to the effectiveness and enthusiasm of student learning during the pandemic in RA Kalipucang District. This study uses a qualitative approach with phenomenological methods, data collection techniques using observation, interviews and documentation. Research resource persons are principals, teachers, students and parents of RA in Kalipucang sub-district, supervisors of early childhood education in Pangandaran Regency and Head of the Ministry of Religion Office ofPangandaran Regency. The analysis technique uses SWOT analysis. The validity test used the source training and technical triangulation methods. The results of the research show that the management of the PAUD learning process in RA Kalipucang District includes three things, namely planning (planning), implementation (actuating) and evaluation (Evaluating). The effectiveness of early childhood learning in RA Kalipucang during the pandemic was more effective using